Investigation of telomerase activity and apoptosis on invasive ductal carcinoma of the breast using immunohistochemical and Western blot methods - Simsek, B. C.; Turk, B. A.; Ozen, F.; Tuzcu, M.; Kanter, M. (Verduci Publisher, 2015)
OBJECTIVE: Invasive ductal carcinoma (IDC) comprises the largest group of breast cancers. This study aimed to investigate telomerase activity and apoptosis using immunohistochemical and Western blot methods. PATIENTS AND METHODS: In total, 75 cases that had been diagnosed as IDC and 20 cases that had undergone a freezing procedure were included. The histological sections were stained with Bax, Bcl-2, hTERT and BNIP3. The ages of the patients, as well as their hormonal status and tumour sizes and grades were evaluated, as well as the staining characteristics of the antibodies in question. RESULTS: A decrease in Bcl-2 positivity and an increase in Bax positivity were found immunohistochemically with increasing tumour grades. The data obtained by western blot method showed that Bcl-2 was highest in grade 1 tumours although these results were not statistically significant. The relationship between estrogen and progesterone receptor positivity and Bcl-2 was statistically significant, suggesting there is hormonal control through apoptosis. BNIP3 was found to be decreased with increasing tumour grades. Similarly, BNIP3 was found to be having the lowest value in grade 3 tumours by western blot method. Furthermore, hTERT was found to be increased with increasing tumour grades. In the western blot method, hTERT increased nearly four-fold compared to the control. In addition, hTERT, which was seen in very high levels in tumours, may be a helpful cancer marker. Both hTERT and BNIP3 are important markers that can provide information about prognosis. CONCLUSIONS: Big improvements can be achieved in tumour progression control with new treatment modalities that stop telomerase activity and hypoxic cell death.
Keywords: Breast; Carcinoma; Apoptosis; Telomerase; Western blot; Immunohistochemistry